2021
DOI: 10.1002/clc.23610
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of calculated Apo‐lipoprotein B in patients with ST‐segment elevation myocardial infarction undergoing primary percutaneous coronary intervention: Outcome is tied to lower cut‐points

Abstract: Background Debates still surround using lipoproteins including Apo‐B in risk assessment, management, and prognosis of patients with coronary artery disease. During an acute ST‐segment elevation myocardial infarction, Apo‐B might help to achieve incremental prognostic information. Objective We sought to determine the potential prognostic utility of calculated Apo‐B in a cohort of patients with STEMI undergoing primary PCI. Methods A retrospective cohort study was conducted enrolling 2,259 patients with a diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…High ApoB was associated with an increased risk of major adverse cardiovascular events (MACEs) in patients with a diagnosis of acute STEMI who underwent primary PCI. 35 Li et al found that the ApoB < 65 mg/day group had a 10% lower risk of long‐term all‐cause mortality when compared with CHD patients with ApoB ≥ 65 mg/dL. 36 Similarly, lower achieved apoB was demonstrated related to lower risk of MACEs in a large population study conducted by Emil et al 37 Besides, a higher level of ApoB was connected with a higher risk of HF.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…High ApoB was associated with an increased risk of major adverse cardiovascular events (MACEs) in patients with a diagnosis of acute STEMI who underwent primary PCI. 35 Li et al found that the ApoB < 65 mg/day group had a 10% lower risk of long‐term all‐cause mortality when compared with CHD patients with ApoB ≥ 65 mg/dL. 36 Similarly, lower achieved apoB was demonstrated related to lower risk of MACEs in a large population study conducted by Emil et al 37 Besides, a higher level of ApoB was connected with a higher risk of HF.…”
Section: Discussionmentioning
confidence: 98%
“…Serum apolipoprotein B to apolipoprotein A-I ratio predicts mortality in patients with heart failure ApoB, which is a key structural element of atherogenic lipoprotein particles including LDL, lipoprotein(a), and triglyceride-rich lipoproteins, is synthesized in the liver and facilitates and amplifies cholesterol transfer in a cycle streaming from the liver to peripheral tissues. 35 A substantial of studies have identified ApoB as the bad apolipoprotein. High ApoB was associated with an increased risk of major adverse cardiovascular events (MACEs) in patients with a diagnosis of acute STEMI who underwent primary PCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 60 Serum level of Lp (a) and serum level of Apo-B showed higher significant prediction for occurrence of CVD. Ghodsi S, 2021 32 Not mentioned Cohort study Coronary heart disease To determine the potential prognostic utility of calculated Apo-B in a cohort of patients with STEMI undergoing primary PCI. NA 2259 Compared to non-HDLC and LDL-C, Apo B appears to be a simple tool for prediction of cardiovascular events in STEMI patients.…”
Section: Introductionmentioning
confidence: 99%